USE OF ALOE VERA GEL AS BIOPRESERVATIVE FOR ‘GRANNY SMITH’ AND ‘REDCHIEF’ APPLES - M. Ergun; F. Satici (Journal of Animal and Plant Sciences, 2012)
The aim of this work was to study effects of Aloe vera gel (0, 1, 5 and 10% w/v) coating on green-coloured ‘Granny Smith’ and red-coloured ‘Red Chief’ apples those were stored at 2 °C for 6 months. Aloe vera gel treatments substantially suppressed the increase in weight loss for ‘Granny Smith’ apples but did not affect weight loss for ‘Red Chief’ apples. Apples from both cultivars softened at definite rates over time, and these rates were not affected from any of the gel treatments. Aloe vera gel treatment suppressed the green colour loss for ‘Granny Smith’ but remained unaffected for ‘Red Chief’ apples. Soluble solids content and percentage titratable acidity was recorded higher for ‘Granny Smith’ apple fruit treated with Aloe vera gel (5 and 10%) during most of the storage period while no Aloe vera gel effects on colour for ‘Red Chief’ apples was recorded. The pH values for ‘Granny Smith’ fruit slightly decreased while slightly increased for ‘Red Chief’ fruit over time, yet values for both cultivars remained unaffected by Aloe vera gel treatments. The results indicated that Aloe vera gel treatment may be used as biopreservative on ‘Granny Smith’ apples for retarding quality losses.
Keywords: Aloe vera gel coating; Grnany Smith; Red Chiebfiop; reservation; apple fruit quality.